Urban-rural relations around the agri-food supply between Ocaña and the municipalities of Catatumbo, as a prospective proposal to the City-Region of Ocaña. (November 2018) - Alba, J; Valdés, D; Durán, S
Abstract: The objective of the study was to identify the urban-rural relations around the agri-food supply between Ocaña and the municipalities of Catatumbo, starting from the geographic identification, products and quantity of food that arrive at the municipal supply center to develop a cartographic representation as the prospective proposal of the City Region of Ocaña. The methodology focused first on the realization of a census in the market place and then to carry out a survey in the supply center of the city. Within the results obtained, it was possible to find that the agro-food relation of Ocaña with the municipalities of Catatumbo is composed of the following municipalities: Teorama, San Calixto, El Carmen, Rio de Oro, Otaré, La Playa, Hacarí, Gonzales, Convention, Abrego and El Tarra. This provide 88.9% of the food arriving in the central market of the city of Ocaña. With the above data, a cartography was generated in which Ocaña's relationship with rural areas is represented, for a city-region proposal.